1971
DOI: 10.6017/ital.v4i4.5596
|View full text |Cite
|
Sign up to set email alerts
|

Title-Only Entries Retrieved by Use of Truncated Search Keys

Abstract: An experiment testing utility of truncated search keys as inquiry terms in an on-line system was performed on a file of 16,792 title-only bibliographic entries. Use of a 3,3 key yields eight or fewer entries 99.0% of the time.A previous paper ( 1) established that truncated derived search keys are efficient in retrieval of entries from a name-title catalog. This paper reports a similar investigation into the retrieval efficiency of truncated keys for extracting entries from an on-line, title-only catalog; it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1972
1972
1992
1992

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Montague (1967), Richard P. Palmer (1972), James Kirkelas (1972), F. W. Lancaster (1977), and Ruth Hafter (1979) have greatly facilitated the evaluation of the literature and selection of materials to be analyzed. Also, reviewers have consistently given high rank to Sidney L. Jackson's Catalog Use Study (1958), Ben-Ami Lipetz's User Requirements in Identifying Desired Works in a Large Library (1970), 'Access and Recognition: From Users' Data to Catalogue Entries' by Renata and Richard P. Palmer's Computerizing the Card Catalogue in the University Library (1972).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Montague (1967), Richard P. Palmer (1972), James Kirkelas (1972), F. W. Lancaster (1977), and Ruth Hafter (1979) have greatly facilitated the evaluation of the literature and selection of materials to be analyzed. Also, reviewers have consistently given high rank to Sidney L. Jackson's Catalog Use Study (1958), Ben-Ami Lipetz's User Requirements in Identifying Desired Works in a Large Library (1970), 'Access and Recognition: From Users' Data to Catalogue Entries' by Renata and Richard P. Palmer's Computerizing the Card Catalogue in the University Library (1972).…”
Section: Methodsmentioning
confidence: 99%
“…As already mentioned, this analysis examines retrieval by single keyword, implied Boolean, and derived truncated search keys having a basic 3,1,1,1 formula for title (Long & Kilgour 1972). Table 4 correlates 1588 card catalog title searches with these three computerized search systems and shows that none of the computerized searches significantly improves upon user success with the card catalog.…”
Section: Reduction In Failure Due To Incorrect and Incomplete Author-mentioning
confidence: 98%
See 1 more Smart Citation
“…A previous paper has shown that truncated three-letter search keys derived from the first two words of a title are less specific than authortitle keys ( 1). Earlier work had revealed that addition of only the first letter of another word in a title improved specificity ( 2) .…”
Section: An Experiments Showing That 3 1 1 1 Search Keys Derived Frmentioning
confidence: 99%
“…A number of papers are available in the literature concerning search key effectiveness; however, all of these were done on relatively small data bases (1)(2)(3)(4)(5) . Of particular importance to this paper is Kilgour's article on truncated search keys ( 6) .…”
Section: Introductionmentioning
confidence: 99%